Immunohistochemical expression of CEA in Head and Neck Squamous and Adenosquamous cell carcinoma (Mustansiria Dental Journal, 2018)
many anatomical sites and is the most common cancer capable of metastatic spread. Development of early diagnosis methods and novel therapeutics are important for prevention and mortality reduction.Aim of the present study was to evaluate the expression of CEA in Head and Neck Squamous cell carcinoma and Adenosquamous carcinoma with the progression of malignant disease.Materials and Methods: Sections of formalin-fixed paraffin embedded blocks specimens of (28)Squamous cell carcinoma and (5) Adenosquamous carcinoma were immunostained to assess the expression of CEA in Head and Neck Squamous cell carcinoma cases.Results: CEA expression was sometimes associated with cytoplasmic staining. The intensity of staining was correlated with the grade of differentiation: grade I was poorly positive staining, while grade III was generally deeply positive stainingConclusions: The immunohistochemical expression of CEA is useful, in addition to other diagnostic criteria, for establishing a differential diagnosis in the case of primary and metastatic cancer.